Empirical models and policy-making : interaction and institutions - Butter, F. A. G. den; Morgan, Mary S. (Routledge, 2000)
This collection provides a picture of how economic modellers and policy makers interact. The book argues that the flow of information is two-way and uses a wealth of international case studies of particular interactions.